(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The greatest significant achievement in dentistry science during the past 100 years may have been the creation of safe and efficient local anaesthetic drugs. The modern dental agents are quite safe and meet the majority of the criteria for an excellent local anaesthetic. These local anaesthetic substances can be used with little risk of causing tissue irritation or adverse responses. There are numerous substances that offer quick onset and sufficient duration of surgical anaesthetic. The drugs offer totally reversible anaesthesia, and systemic toxicity is infrequently recorded. There is currently no perfect local anaesthetic drug that can selectively inhibit pain pathways to cause localised analgesia without affecting the transmission of other sensory modalities. This issue of Dental Clinics of North America gives a summary of recent developments in local anaesthetic therapies that are now employed in dentistry and sheds light on a variety of issues regarding the substances used for local anaesthesia. In this introduction, the clinical pharmacology of the current local anaesthetic drugs and formulations used in dentistry is briefly updated. This update is followed by a discussion of the dosing methods required to avoid local anaesthetic toxicity reactions.